2009
DOI: 10.1002/ijc.24531
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of caveolin‐1 and CD147 expression in nasopharyngeal carcinoma enhanced tumor cell migration and correlated with poor prognosis of the patients

Abstract: Expression of caveolin-1 (Cav-1) and extracellular matrix metalloproteinase inducer (EMMPRIN/CD147) and their prognostic significance were analyzed in archive NPC samples. Cav-1 and CD147 were overexpressed in 49. 48% (96/194) and 59.39% (117/ 197) of NPC, respectively. Both Cav-1 and CD147 expression levels correlated significantly with metastasis (p 5 0.025 and 0.017, respectively) and a lower 5-year survival rate (p 5 0.02 and 0.0009, respectively). In addition, Cav-1 expression levels correlated signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…Moreover, studies in samples derived from esophageal squamous cell carcinoma (Ando, Ishiguro et al 2007), small cell lung carcinomas , colon cancer cells with elevated metastatic potential ( (Bender, Reymond et al 2000), see below) and gastric cancer (Burgermeister, Tencer et al 2003), revealed that caveolin-1 expression correlates with poor patient prognosis. Furthermore, caveolin-1 is also overexpressed in nasopharyngeal carcinoma and protein levels correlate there with poor prognosis, enhanced tumor cell migration and metastasis (Du, Hu et al 2009). Finally, caveolin-1 was recently associated with tumor progression in a panel of melanoma cell lines, since increased expression correlated with enhanced proliferation, cell migration and tumorigenicity (Felicetti, Parolini et al 2009).…”
Section: Role Of Caveolin-1 As Tumor Suppressor: Inhibition Of β-Catementioning
confidence: 99%
“…Moreover, studies in samples derived from esophageal squamous cell carcinoma (Ando, Ishiguro et al 2007), small cell lung carcinomas , colon cancer cells with elevated metastatic potential ( (Bender, Reymond et al 2000), see below) and gastric cancer (Burgermeister, Tencer et al 2003), revealed that caveolin-1 expression correlates with poor patient prognosis. Furthermore, caveolin-1 is also overexpressed in nasopharyngeal carcinoma and protein levels correlate there with poor prognosis, enhanced tumor cell migration and metastasis (Du, Hu et al 2009). Finally, caveolin-1 was recently associated with tumor progression in a panel of melanoma cell lines, since increased expression correlated with enhanced proliferation, cell migration and tumorigenicity (Felicetti, Parolini et al 2009).…”
Section: Role Of Caveolin-1 As Tumor Suppressor: Inhibition Of β-Catementioning
confidence: 99%
“…CAV1 (caveolin 1, caveolae protein, 22kDa) plays a role in the formation of caveolae that are small lipid rafts responsible for vesicle trafficking, cholesterol homeostasis and signal transduction. High CAV1 levels have been linked with the metastatic phenotype as they lead to the secretion of MMP3 and MMP11 (matrix metalloproteinases 3 and 11) [30]. High CAV1 levels are also observed in MDA-MB-231 cells compared to MCF-7 cells in the expression profile in Figure 4F.…”
Section: Discussionmentioning
confidence: 94%
“…Even in the same histology type such as SCC, Cav-1 also has a different expression pattern. In vivo study of tongue (7), esophagus (8,18), bladder (21), lung (22) and nasopharynx (23) SCC demonstrated overexpression of Cav-1 protein in the tumour cells, and is closely correlated with tumor progression and poor prognosis (18,23). Nevertheless, in the primary head and neck squamous cell carcinoma (HNSCC), Cav-1 may play an inhibitory role in tumourigenesis and lung metastasis (24).…”
Section: Discussionmentioning
confidence: 99%